EFEKTIVITAS KONSELING KELOMPOK TEKNIK RELAKSASI UNTUK MEREDUKSI KECEMASAN SISWA MENGHADAPI UJIAN DI SMP PGRI 1 PALEMBANG - Arizona Arizona; Nurlela Nurlela; Zilla Jannati (Jurusan Bimbingan dan Konseling, 2019)
The purpose of this study are: (1) to determine the effectiveness of group counseling and reduce anxiety students face the test, (2) to determine the effectiveness of group counseling models with relaxation techniques to reduce students' anxiety in facing the exam. This type of research is quantitative research with experimental research design , using the initial test design (pretest) and the final treatment (posttest). This research involved PGRI 1 Palembang junior high school students. The steps taken are: (1) preparation of the experimental group, (2) giving the pretest in the experimental group (3) giving tretment or treatment to the experimental group (4) giving post test in the experimental group, (5) the final effectiveness of group counseling with relaxation techniques assisted by instrumental music to reduce the anxiety of students facing exams. The analysis was carried out using the Wilcoxon test. Based on the results of the field test, the level of anxiety students face the test has decreased after participating in group counseling activities with relaxation techniques. Shown by changes in the level of anxiety of students facing the pre-test (initial evaluation) and post-test (final evaluation) that is equal to 84% (pre) to 45% (post). Wilcoxon test results obtained Asymp.sig. (2-tailed) of 0.008 with a significant 5% (<0.05) so that it can be concluded that group counseling services with relaxation techniques assisted by instrumental music are effective to reduce students' anxiety in facing the exam keywords: group counseling. Relaxation, instrumental music, anxiety